2019
DOI: 10.3389/fncom.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of High-Frequency Oscillations in Epilepsy Based on a Convolutional Neural Network

Abstract: Epilepsy is one of the most common chronic neurological diseases. High-frequency oscillations (HFOs) have emerged as promising biomarkers for the epileptogenic zone. However, visual marking of HFOs is a time-consuming and laborious process. Several automated techniques have been proposed to detect HFOs, yet these are still far from being suitable for application in a clinical setting. Here, ripples and fast ripples from intracranial electroencephalograms were detected in six patients with intractable epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 43 publications
2
56
1
Order By: Relevance
“…Approximate entropy has been used as a feature to identify HFOs with respect to baseline segments: during an HFO, the complexity of the signal is higher, therefore its approximate entropy is higher. Finally, a convolutional neural network (CNN) has been used for automatic detection of ripples and fast ripples [30]. The CNN's performance has been compared with the four reference-detectors collected in the RIPPLELAB application [31] and showed much higher sensitivity (77.04% for ripples and 83.23% for fast ripples) and specificity (72.27% for ripples 79.36% for fast ripples) except than the specificity of Staba detector [7] for ripples (83.14%) and the sensitivity of the MNI detector [6] for fast ripples (74.77%).…”
Section: Introductionmentioning
confidence: 99%
“…Approximate entropy has been used as a feature to identify HFOs with respect to baseline segments: during an HFO, the complexity of the signal is higher, therefore its approximate entropy is higher. Finally, a convolutional neural network (CNN) has been used for automatic detection of ripples and fast ripples [30]. The CNN's performance has been compared with the four reference-detectors collected in the RIPPLELAB application [31] and showed much higher sensitivity (77.04% for ripples and 83.23% for fast ripples) and specificity (72.27% for ripples 79.36% for fast ripples) except than the specificity of Staba detector [7] for ripples (83.14%) and the sensitivity of the MNI detector [6] for fast ripples (74.77%).…”
Section: Introductionmentioning
confidence: 99%
“…The result showed in the above section that the selection of prominent features and the oversampling method can significantly improve the performance of an automatic system. Hence, we are the first one to use high-frequency components (ripple and fast ripple) from interictal iEEG, the performances of localizing individual segments were observed in terms of sensitivity, specificity, precision, fallout, and F-score for the comparison study similar to HFOs-and low frequency-based related studies 10,[19][20][21][31][32][33][34][35] computed from the confusion matrix (shown in Table 6). It is observed from the Table 2 that the proposed method achieved the highest performance for localizing individual segments with the adult patients Pt5 (SEN: 79.25%; fall-out: 2.50%), Pt6 (SEN: 54.82%; fall-out: 3.58%), and Pt8 (SEN: 88.52%; fall-out: 1.46%).…”
Section: Resultsmentioning
confidence: 99%
“…31 . Zuo et al 33 proposed the CNN-based method for identifying the two kind of HFOs in ripple and fast-ripple separately and achieved average results with sensitivity (77.04% and 83.23% for ripples) and specificity (72.27% and 79.36% for fast ripples) compared to four traditional automated methods proposed in the RIPPLELAB toolbox 32 . The combination of short-time energy (STE) and CNN also used in recent study for identifying HFOs 62 .…”
Section: Discussionmentioning
confidence: 99%
“…RippleNet's implementation differs from Zuo et al 2019, one of very few deep CNN based algorithms specifically designed for detection of high-frequency oscillations (HFO), that is, epileptogenic zone seizures in intracranial electroencephalogram (iEEG) recordings, in that (1) explicit conversion of 1D input sequences with multiple rows into gray-scale images are avoided;…”
Section: Introductionmentioning
confidence: 99%